The long-term impact of urbanization on nitrogen patterns and dynamics in Shanghai, China - Gu, Baojing; Dong, Xiaoli; Peng, Changhui; Luo, Weidong; Chang, Jie; Ge, Ying (Environmental Pollution, 2012)

Weak indirect effects inherent to nitrogen biogeochemical cycling within anthropogenic ecosystems: A network environ analysis - Min, Yong; Jin, Xiaogang; Chang, Jie; Peng, Changhui; Gu, Baojing; Ge, Ying; Zhong, Yang (Ecological Modelling, 2011)

Anthropogenic modification of the nitrogen cycling within the Greater Hangzhou Area system, China - Gu, Baojing; Chang, Jie; Ge, Ying; Ge, Hanliang; Yuan, Chi; Peng, Changhui; Jiang, Hong (Ecological Applications, 2009)
Based on the mass balance approach, a detailed quantification of nitrogen (N) cycling was constructed for an urban–rural complex system, named the Greater Hangzhou Area (GHA) system, for this paper. The GHA is located in the humid climatic region on the southeastern coast of China, one of the earliest regions in the Yangtze Delta to experience economic development. Total N input into the GHA was calculated at 274.66 Gg/yr (1 Gg = 10 9 g), and total output was calculated at 227.33 Gg/yr, while N accumulation was assessed at 47.33 Gg/yr (17.2% of the total N input). Human activity resulted in 73% of N input by means of synthetic fertilizers, human food, animal feed, imported N containing chemicals, fossil fuel combustion, and other items. More than 69.3% of N was released into the atmosphere, and riverine N export accounted for 22.2% of total N output. N input and output to and from the GHA in 1980 were estimated at 119.53 Gg/yr and 98.30 Gg/yr, respectively, with an increase of 130% and 131%, respectively, during a 24‐year period (from 1980 to 2004). The N input increase was influenced by synthetic fertilizers (138%), animal feed (225%), N‐containing chemicals (371%), riverine input (311%), and N deposition (441%). Compared to the N balance seen in the arid Central Arizona–Phoenix (CAP) system in the United States, the proportion of N transferred to water bodies in the humid GHA system was found to be 36 times higher than the CAP system. Anthropogenic activity, as it typically does, enhanced the flux of N biogeochemistry in the GHA; however, a lack of an N remover (N pollutant treatment facilities) causes excess reactive N (N r ; such as NH 3 , N 2 O, NO x ), polluting water bodies and the atmosphere within the GHA. Therefore many challenges remain ahead in order to achieve sustainable development in the rapidly developing GHA system.

The role of industrial nitrogen in the global nitrogen biogeochemical cycle - Gu, Baojing; Chang, Jie; Min, Yong; Ge, Ying; Zhu, Qiuan; Galloway, James N.; Peng, Changhui (Scientific Reports, 2013)

Does growing vegetables in plastic greenhouses enhance regional ecosystem services beyond the food supply? - Chang, Jie; Wu, Xu; Wang, Yan; Meyerson, Laura A; Gu, Baojing; Min, Yong; Xue, Hui; Peng, Changhui; Ge, Ying (Frontiers in Ecology and the Environment, 2013)
In recent years, plastic greenhouse vegetable cultivation (PGVC) has expanded worldwide, particularly in China, where it accounts for more than 90% of all global PGVC operations. As compared with conventional agricultural methods, PGVC has doubled crop yields by extending growing seasons and intensifying agriculture. PGVC also offers more ecosystem services relative to conventional approaches, including greater soil carbon sequestration, lower water consumption, and improved soil protection at regional scales. The economic benefits of this easily implemented agricultural method are attractive to small‐holder farmers. However, greater environmental impacts (eg greenhouse‐gas emissions, generation of large amounts of plastic waste) are associated with PGVC than with conventional approaches. Here, we review what is currently known about PGVC and identify future research priorities that will comprehensively assess the ecosystem services offered by this method of cultivation, as well as its environmental impacts and socioeconomic benefits.

The effects of plant diversity on nitrous oxide emissions in hydroponic microcosms - Sun, Hongying; Zhang, Chongbang; Song, Changchun; Chang, Scott X.; Gu, Baojing; Chen, Zhengxin; Peng, Changhui; Chang, Jie; Ge, Ying (Atmospheric Environment, 2013)

The role of technology and policy in mitigating regional nitrogen pollution - Gu, Baojing; Zhu, Yimei; Chang, Jie; Peng, Changhui; Liu, Dong; Min, Yong; Luo, Weidong; Howarth, Robert W; Ge, Ying (Environmental Research Letters, 2011)

Constructed wetlands as biofuel production systems - Liu, Dong; Wu, Xu; Chang, Jie; Gu, Baojing; Min, Yong; Ge, Ying; Shi, Yan; Xue, Hui; Peng, Changhui; Wu, Jianguo (Nature Climate Change, 2012)

Quantification of net carbon flux from plastic greenhouse vegetable cultivation: A full carbon cycle analysis - Wang, Yan; Xu, Hao; Wu, Xu; Zhu, Yimei; Gu, Baojing; Niu, Xiaoyin; Liu, Anqin; Peng, Changhui; Ge, Ying; Chang, Jie (Environmental Pollution, 2011)

Agricultural carbon flux changes driven by intensive plastic greenhouse cultivation in five climatic regions of China - Wu, Xu; Ge, Ying; Wang, Yan; Liu, Dong; Gu, Baojing; Ren, Yuan; Yang, Guofu; Peng, Changhui; Cheng, Jihua; Chang, Jie (Journal of Cleaner Production, 2015)

Assessment of net ecosystem services of plastic greenhouse vegetable cultivation in China - Chang, Jie; Wu, Xu; Liu, Anqin; Wang, Yan; Xu, Bin; Yang, Wu; Meyerson, Laura A.; Gu, Baojing; Peng, Changhui; Ge, Ying (Ecological Economics, 2011)

Assessment of private economic benefits and positive environmental externalities of tea plantation in China - Xue, Hui; Ren, Xiaoyi; Li, Shiyu; Wu, Xu; Cheng, Hao; Xu, Bin; Gu, Baojing; Yang, Guofu; Peng, Changhui; Ge, Ying; Chang, Jie (Environmental Monitoring and Assessment, 2013)